Voluntary Assisted Dying: The Impasse and a Way Forward - Dankwort, Juergen (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
The project to provide voluntary assisted dying (VAD) has grown significantly and at an accelerating rate over the past two decades in over 30 countries on four continents. Yet, concomitant with this rise is an increasing opposition to it based on legal, medical, and ethical grounds advanced by a wide range of detractors, giving pause to projects already underway, and bringing its enlargement to a halt. Simultaneously, persons seeking relief from suffering continue to be denied VAD access or are forced to wait for it by decreed compulsory living. Those assisting beyond the legislated parameters of a VAD regime are facing criminal prosecution. The contraposition to VAD has raised the risk of desperate persons seeking relief by committing violent suicide, endangering family, friends, and first responders. In light of this concerning development, I identify how the prevailing legislated approach at the source of these issues is both paradigmatic and problematic. Amendments to existing prohibitions for assisted dying or homicide become the foundation of an assisted dying regime that codifies its essential features, including client typology, life quality for service access or its denial, who is authorized to provide VAD, and when and how it can be administered. While this approach continues to be replicated extensively and has provided some relief to unbearable living, I show how an alternative, time-tested, evidence-based approach for VAD offers an optional pathway that could avoid many of the most challenging aspects of the prevalent model.